2018
DOI: 10.1007/s11292-018-9346-2
|View full text |Cite
|
Sign up to set email alerts
|

An experimental trial of a dog-training program in a juvenile detention center

Abstract: Objectives: This research examines the effect of a dog-training program among juveniles ordered to a county juvenile detention facility in a large, Midwestern city. Methods: A pre-test, post-test experimental design was constructed to examine changes in selfesteem, empathy, optimism, pessimism, compassion, and social competence between juveniles who were randomly assigned to the canine-assisted activity program and to the standard conditions of the detention center without access to the program. Two-way and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…The lack of overall improvement in primary and secondary outcomes as a result of DCD participation is consistent with the results of two RCT’s on DTPs for youth offenders that did not find positive program effects in externalizing behavioral problems ( Seivert et al, 2016 ) and in psychosocial functioning (i.e., self-esteem, empathy, optimism, pessimism, compassion, and social competence; Grommon et al, 2018 ; Seivert et al, 2016 ). This is in contrast with previous research in adults, that did demonstrate positive overall effects for DTPs in primary (i.e., infractions, externalizing behavior problems; e.g., Cooke & Farrington, 2016 ; van Wormer et al., 2017 ) and secondary outcomes, such as social-emotional (e.g., Cooke, 2014 ) and therapeutic (e.g., Fournier et al., 2007 ) functioning.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The lack of overall improvement in primary and secondary outcomes as a result of DCD participation is consistent with the results of two RCT’s on DTPs for youth offenders that did not find positive program effects in externalizing behavioral problems ( Seivert et al, 2016 ) and in psychosocial functioning (i.e., self-esteem, empathy, optimism, pessimism, compassion, and social competence; Grommon et al, 2018 ; Seivert et al, 2016 ). This is in contrast with previous research in adults, that did demonstrate positive overall effects for DTPs in primary (i.e., infractions, externalizing behavior problems; e.g., Cooke & Farrington, 2016 ; van Wormer et al., 2017 ) and secondary outcomes, such as social-emotional (e.g., Cooke, 2014 ) and therapeutic (e.g., Fournier et al., 2007 ) functioning.…”
Section: Discussionsupporting
confidence: 78%
“… Seivert et al (2016) found that anxiety and empathy worsened slightly overtime in both the DTP and active control group; no changes were found in externalizing behavioral problems. Grommon et al (2018) found no change in a variety of psychosocial factors (e.g., self-esteem, empathy, compassion, social competence) after participation in a DTP. Chianese (2009) , on the other hand, concluded that DTPs are a promising intervention for incarcerated adolescent girls, as program participants reoffended at only half the rate compared to girls who had no dog contact.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Several types of PBDPs exist (e.g., Grommon et al, 2018; Jasperson, 2013). One of these is the dog-training program (DTP), in which individuals who are incarcerated train asylum dogs, equipping them for adoption (i.e., community service design), or train dogs to become assistance dogs for people with disabilities or mental health problems (i.e., service animal socialization program; Furst, 2006).…”
Section: Introductionmentioning
confidence: 99%